Analysis of Factors Affecting Financial Well Being Millennial Generation in Batam - Yandi Suprapto (Journal of Global Business and Management Review, 2020)
The purpose of this study is to determine whether financial behavior, financial socialization agents, financial attitude, financial stress, and financial literacy can influence financial well being in millennial generation in Batam City. Financial well being is described when a person is able to prosper in the field of financial finance. Welfare is reflected in the ability to meet and manage all needs and desires. While millennial is the most current generation so that it can be a hope and reflection of a country. This research method begins with the distribution of questionnaires to the people of Batam city aged 15-19 years. Data were collected as many as 300 respondents then processed with multiple regression research models using SPSS. Variable financial literacy, financial attitude and financial socialization agents provide a significant positive relationship to financial well being. Meanwhile financial stress has a significant negative relationship with financial well being. Then for financial behavior variables show no significant relationship to financial well being.